2020
DOI: 10.1128/aem.01337-20
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Rice Planthopper Populations by the Entomopathogenic Fungus Metarhiziumanisopliaewithout Affecting the Rice Microbiota

Abstract: Entomopathogenic fungi can regulate insect populations and function as crucial biological control agents against insect pests, but their impacts on nontarget microorganisms are poorly understood. In this study, we investigated the potential of the fungal strain Metarhizium anisopliae CQMa421 to control rice planthoppers under field conditions and its effects on rice microbiota. This fungus suppressed rice planthoppers during this period, and its control efficiency was more than 60% 7 days post application and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…The overall mean efficacy of RPH control by either fungal insecticide in three field trials was significantly higher in the treatment of UVavo (~77%) than of UVexp (~65%) on day 14 after the first spray. These observations were in agreement with the RPH control efficacy of 50-70% observed in the previous field trials of M. anisopliae CQ421 under undisclosed weather conditions [32,33]. The repeated spray of each fungal insecticide provided a consistent RPH control for two more weeks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall mean efficacy of RPH control by either fungal insecticide in three field trials was significantly higher in the treatment of UVavo (~77%) than of UVexp (~65%) on day 14 after the first spray. These observations were in agreement with the RPH control efficacy of 50-70% observed in the previous field trials of M. anisopliae CQ421 under undisclosed weather conditions [32,33]. The repeated spray of each fungal insecticide provided a consistent RPH control for two more weeks.…”
Section: Discussionsupporting
confidence: 91%
“…Application of B. bassiana granules to the water surface in contact with rice plants led to as effective an RPH control as a spray of conidia under controlled conditions [31]. Field trials with a formulation of M. anisopliae CQ421 showed a RPH control efficacy of 50-70% on day 7 after spraying and little impact on native microbiota [32,33]. The same formulation has also proved effective for the sustainable control of major rice insect pests, including leaf folders and stem borers as well as RPH, with minimal effects on natural enemies of those pests, in multiple provinces of China during 2011-2018 [34].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we isolated the fungal M. anisopliae strain CQMa421 to challenge N. lugens nymphs and adults, which resulted in high mortality. Additionally, this fungus has been suggested for use in long-term control under field conditions and has relatively limited effects on nontargets species (i.e., microbial diversity and structure) [ 22 ]. Although a few studies focused on the transcriptomic level of N. lugens under stressful conditions, less attention has been paid to the analysis of this fungus at the posttranscriptional level, especially under entomopathogenic fungal challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found that the fungus M. anisopliae CQMa421 exhibited great potential for the control of major rice pests, including the rice planthopper N. lugens [ 21 ]. This fungal agent can also suppress the population of rice planthoppers to a low level under field conditions [ 22 , 23 ]. However, the underlying molecular interactions between the rice planthopper and the fungus are poorly understood, although this knowledge may enhance potential fungal agents for other pest control.…”
Section: Introductionmentioning
confidence: 99%